2021
DOI: 10.1051/0004-6361/202039046
|View full text |Cite
|
Sign up to set email alerts
|

A Virgo Environmental Survey Tracing Ionised Gas Emission (VESTIGE)

Abstract: We study the IB(s)m galaxy IC 3476 observed in the context of the Virgo Environmental Survey Tracing Ionised Gas Emission (VESTIGE), a blind narrow-band Hα+[NII] imaging survey of the Virgo cluster carried out with MegaCam at the CFHT. The deep narrow-band image reveals a very pertubed ionised gas distribution that is characterised by a prominent banana-shaped structure in the front of the galaxy formed of giant HII regions crossing the stellar disc. Star-forming structures, at ∼8 kpc from the edges of the ste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
98
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(113 citation statements)
references
References 148 publications
15
98
0
Order By: Relevance
“…Moreover, the HI mass of AGC 226178 from Cannon et al (2015) (M HI = 4 × 10 7 M ) corresponds to ∼10% of the mass of the gas expected to be stripped from NGVS 3543 as indicated by the models. Considering that in similar RPS events a large fraction of the stripped gas can also change phase, becoming ionized gas before hot gas (Boselli et al 2016(Boselli et al , 2021, our analysis is consistent with the gas detected as AGC 226178 having been recently stripped from NGVS 3543 during the RPS event.…”
Section: An Udg Undergoing a Rps Eventsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, the HI mass of AGC 226178 from Cannon et al (2015) (M HI = 4 × 10 7 M ) corresponds to ∼10% of the mass of the gas expected to be stripped from NGVS 3543 as indicated by the models. Considering that in similar RPS events a large fraction of the stripped gas can also change phase, becoming ionized gas before hot gas (Boselli et al 2016(Boselli et al , 2021, our analysis is consistent with the gas detected as AGC 226178 having been recently stripped from NGVS 3543 during the RPS event.…”
Section: An Udg Undergoing a Rps Eventsupporting
confidence: 84%
“…For the confirmed tail regions, Kenney et al (2014) obtained ages ranging from 80 to 390 Myr, consistent with the quenching time from their models. In the tail of NGC 4254, which is likely the result of tidal interactions, Boselli et al (2018a) estimate an age of ≤100 Myr for typical star forming regions, whereas for the tail of a recently ram-pressure stripped (∼50 Myr ago) dwarf galaxy IC 3476, Boselli et al (2021) give a typical age of ≤20 Myr for a few star forming complexes observed in the tail at ∼8 kpc from the stellar disk.…”
Section: Ages and Stellar Masses Of The Young Regionsmentioning
confidence: 99%
“…This suggests that Hα + [Nii] emission, and therefore star formation, is enhanced along the leading side of the jellyfish galaxies, consistent with gas compression induced by ram pressure along the galaxy-ICM interface. As alluded to in Section 3, such an effect has been predicted by simulations of RPS (e.g., Bekki 2014;Troncoso-Iribarren et al 2020) and been reported observationally for a limited number of galaxies experiencing ram pressure (e.g., Gavazzi et al 2001;Boselli et al 2021). Further work is required to test whether these leading-side star formation enhancements are commonplace for galaxies undergoing RPS, and the results reported here are a step in that direction.…”
Section: Hα + [Nii] Sources Relative To Tail Directionsupporting
confidence: 63%
“…Ram pressure can influence galaxy star formation both by removing cold gas (leading to rapid quenching) and by driving increased densities in the interstellar medium (ISM), potentially leading to starburst behavior (e.g., Schulz & Struck 2001;Bekki 2014;Vulcani et al 2018;Roberts & Parker 2020;Cramer et al 2021). The latter is predicted to occur on the "leading-side" of galaxies undergoing RPS, in other words, the side of the galaxy directly encountering the intracluster medium (ICM), opposite to the stripped tail (e.g., Gavazzi et al 2001;Boselli et al 2021). In order to place strong constraints on the effect of RPS on star formation within galaxies (i.e., Is star formation quenched from the outside-in?…”
Section: Introductionmentioning
confidence: 99%
“…Ram pressure stripping only affects gas, not stars, and therefore it is probable that these galaxies underwent some gravitational interactions too, capable of removing stars as well as gas. An increase in star formation due to ram pressure is only possible in the case of an almost edge-on interaction of a galaxy into the intracluster medium: the gas moves towards the disk before being removed from the galaxy, this leads to compression of the gas and therefore a burst of star formation as observed in IC3476 (Boselli et al 2021). This burst is relatively short -as the stripping process is rapid (<500 Myr)-and is thus statistically difficult to observe.…”
Section: Selection Of Hrs Quenched Galaxiesmentioning
confidence: 99%